Consumption, habit persistence, imperfect information and the lifetime budget constraint - Alpo Willman (European Central Bank (ECB), 2003)
Based on the households' utility maximisation, a closed form approximation of the consumption function is derived and the deep parameters of the consumption function are estimated using aggregate euro area data. The novel element in our approach is the parameterisation of the information content regarding future income changes. In addition to the information regarding time series properties of the historical development of labour income, consumers have also period-specific information on future income realisations. Estimation results support the hypothesis that, although front-loaded, consumers have a lot of information on future income changes, but that also lagged consumption, through habit formation, plays an important role.
Keywords: D12; E21; 330; Consumption; life-cycle hypothesis; wealth